FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA RETENSI PERAWAT DI RS-IA ROSIVA MEDAN - Yosafat Barus, Fridella Grace Natalia Tarigan, Yosafat Barus (JURNAL PIONIR, 2021)
ABSTRACT Retention of nurses is one measure of the success of the hospital especially the management of human resources and nursing manage and retain nurse. Nurses will be comfortable and productive at work if it met the diverse needs of both physically. Fulfillment of physical and psychological and psychological needs may depend on several factors, among others, the factors compensation, career development, selection employment and job satisfaction. This research is descriptive correlative, and this research aim to know The factors that affect the retention of nurses in the RS-IA Rosiva in 2019. The type of the research was univariat, the study was conducted using a questions, population in this study ware 30 respondents and a sample of this research is total sampling using Guttman scale data processing is done with the editing, coding, data entry, and analysis techniques. After conducting research in the RS-IA Rosiva nurses found that the frequency distribution of the compensation received is the greatest thing in which the majority of compensation is not satisfied as much as 17 respondents (56,6%) and minority are satisfied as much as 13 respondents (43,3%). This study is the input that the factors that need to be highly correlated retained and enhanced. Key Word : Retention, Nurse. PENDAHULUAN Get Les Mckeown’s (2010) mendefenisikan retensi sebagai usaha sistem matis oleh majikan untuk menciptakan dan mendorong lingkungan yang membuat pekerja tetap bertahan ditempat mereka sekarang. Isu retensi tidak hanya menjadi permasalahan dinegara berkembang, tetapi juga menjadi isu besar di Negara-negara maju.( didalam Kurniati, 2012 ). Salah satu fungsi yang penting pada manajemen sumber daya manusia adalah fungsi pemeliharaan disamping fungsi lainnya yaitu fungsi perencanaan, pengorganisasian, pengarahan, pengendalian, pengadaan, pengembangan, kompensasi, p